2017
DOI: 10.3892/ol.2017.7427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wnt‑1 blockade in DEN‑induced hepatocellular adenomas of mice

Abstract: Abstract. Recent evidence has suggested that downregulation of the Wnt/β-catenin signaling pathway may contribute to the development and growth of HCC. Consequently, elements of this pathway have begun to emerge as potential targets for improving outcomes of anti-HCC. Thus, the present study sought to examine the effects of Wnt-1 blockade using the classical diethylnitrosamine (DEN)-induced chemical carcinogenesis mouse model of HCC. The depletion of Wnt-1 using neutralizing antisera was done for ten consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…HDACi were shown to play a crucial role in cancer progression through regulation of cell proliferation and apoptosis. 33 Although apoptosis has been reported to be a rare event in early HCC lesions in mouse, 29,30 in our study despite the low number of apoptotic cells, morphometric analysis revealed a significant increase of Caspase-3-positive (apoptotic) neoplastic cells in Romidepsin-treated HCC mice, as compared to their non-treated counterparts, which supports a role of Romidepsin in promoting apoptosis. 23 This was further strengthened by the significant elevation of BAD, a major apoptosis regulator, detected in serum of Romidepsin-treated mice, as compared to the HCC untreated controls.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…HDACi were shown to play a crucial role in cancer progression through regulation of cell proliferation and apoptosis. 33 Although apoptosis has been reported to be a rare event in early HCC lesions in mouse, 29,30 in our study despite the low number of apoptotic cells, morphometric analysis revealed a significant increase of Caspase-3-positive (apoptotic) neoplastic cells in Romidepsin-treated HCC mice, as compared to their non-treated counterparts, which supports a role of Romidepsin in promoting apoptosis. 23 This was further strengthened by the significant elevation of BAD, a major apoptosis regulator, detected in serum of Romidepsin-treated mice, as compared to the HCC untreated controls.…”
Section: Discussionsupporting
confidence: 70%
“…With Caspase-3-specific IHC we first found that apoptotic cells in HCC lesions are particularly scarce, which matches our previous observations in DEN-induced early hepatocellular carcinogenesis. 29,30 Notably, morphometric counts of Caspase-3-positive cancer cells suggested that HDAC1/2 inhibition upregulates apoptosis in HCC at statistically significant levels (Figure 2). Likewise, using the proliferation marker Ki-67, we found that HCC tumors of Romidepsin-treated mice contained significantly less Ki-67-positive cancer cells compared to their untreated counterparts (Figure 2A).…”
Section: Hdac1/2 Inhibition Affects Apoptosis and Proliferation Of Hcc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…An anti-Wnt1-antibody has been found to inhibit Wnt/β-catenin signaling and tumor growth in a xenograft mouse model (Wei et al, 2009). In contrast, anti-Wnt1 suppressed proliferation and apoptosis, but did not affect tumor size and growth in diethylnitrosamine-induced hepatocellular adenomas (Sklavos et al, 2018). Interestingly, garlic-derived compound S-allylmercaptocysteine reduced HCC tumorigenesis by directly targeting Lrp6 at the plasma membrane (Xiao et al, 2018).…”
Section: Liver Cancermentioning
confidence: 99%
“…HCC model was induced by intraperitoneal (i.p.) injection with one dose of DEN (Sigma-Aldrich, St. Louis, MO) at 20 mg·kg -1 body weight, while the normal mice received an equivalent volume of sterilized saline instead 17 . After 40 weeks, all mice were performed euthanasia sacrificed after collecting blood.…”
Section: Methodsmentioning
confidence: 99%